The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/trf.15869
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of hospital‐based blood collections in the face of COVID‐19 associated national blood shortage

Abstract: BACKGROUND: When the coronavirus pandemic caused widespread school and business closures in March 2020, blood drives were cancelled and the supply of blood decreased suddenly in the United States (US). In response, hospital-based transfusion medicine physicians instituted policies to conserve blood and decrease blood product usage. These efforts were aided by the US Surgeon General recommendation to cancel all elective procedures. Nevertheless, the duration, severity, and impact of the pandemic on the national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 5 publications
2
31
0
5
Order By: Relevance
“…Gniadek et al studied the impact of the cancellation of elective surgeries and procedures on the demands for blood components [11]. They found that it only led to a modest, non-significant decline in the demand for packed RBCs, platelets, and FFP units.…”
Section: Strategies To Replenish Drying Blood Storesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gniadek et al studied the impact of the cancellation of elective surgeries and procedures on the demands for blood components [11]. They found that it only led to a modest, non-significant decline in the demand for packed RBCs, platelets, and FFP units.…”
Section: Strategies To Replenish Drying Blood Storesmentioning
confidence: 99%
“…They found that it only led to a modest, non-significant decline in the demand for packed RBCs, platelets, and FFP units. To tackle this crisis, the transfusion medicine department at NorthShore University HealthSystem, Evanston, Chicago ramped up the in-house donor programs which led to a 5-fold increment in the storage for whole blood units [11]. has also requested the general public to come forward for blood donation [12].…”
Section: Strategies To Replenish Drying Blood Storesmentioning
confidence: 99%
“…Maintaining adequate supplies of safe blood in order to guarantee the execution of necessary surgical procedures or other medical activities can prove to be particularly difficult in emergency situations, especially epidemics. In the first few months of the pandemic, many countries [ 51 ], including Italy [ 52 ], experienced a consistent decrease in donations and, therefore, in the availability of hematic products. Although to date there is no evidence to suggest the possibility of virus transmission through blood from symptomatic individuals, the shortage is due to the greater difficulty in travel, the risks associated with congregating in donation centers, and a higher percentage of the population that is potentially infected and unable to donate.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced LOS increases bed availability and the ability to accommodate increases in patient volume. Fewer bleeding events allows for conservation of scarce blood products [18]. These positive outcomes by PERT occurred without a complete understanding of the pathophysiology of COVID-19 or evidence-based management guidelines.…”
Section: Discussionmentioning
confidence: 99%